(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
The basic objective of the paper is to reconcile the literature on knowledge management and supply Chain management in organizations. The paper build strategy formulation, the inputs to strategy formulation process are the results of evaluating e-business technology, the business environment, plus knowledge management and Supply-Chain management to dig out the important relationships and flows of activities. Theoretical relationships are enriched by the conclusions drawn from literature review. It includes Supply-Chain management and Knowledge management. By studying conceptual studies, we find that different components of Knowledge Management as Knowledge activities, Knowledge types, transformation of knowledge and technology have a significant positive effect in bringing strategies through transformation of knowledge into knowledge assets in organizations. The strategy diagram divides implementation into the technical and the business aspects.